The Role of Insurance Relation Doctors in Reducing the Waiting Time for Inpatient Discharge: An Observational Study - Bernadette, Jesslyn; Bashabih, Masyitoh (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Waiting time for patient discharge is a key indicator in determining the quality of hospital services. In an effort to improve waiting time for patient discharge, some hospitals recruit insurance relation doctors to help check discharge paperwork, especially for patients with insurance coverage. This study aims to see the role of insurance relation doctors in reducing the waiting time for inpatient discharge. This study is an observational study with a cross-sectional study design. Waiting time data was taken through the hospital system and analyzed univariately and bivariately using the independent t-statistical test. Univariate data showed a decrease in the waiting time for inpatient discharge by 5% after the insurance relation doctor joined. However, the statistical test results showed that there was no significant relationship (CI 95% p>0.05) between the joining of insurance relation doctors and the decrease in the waiting time for inpatient discharge. The role of insurance relations doctors has yet to have a significant effect in reducing waiting time for discharge, possibly due to the short duration of the intervention, the involvement of many parties, and the workload of insurance relations doctors. Further research is needed regarding the details of the inpatient discharge process and the productivity of insurance relations doctors in carrying out their roles in the hospital.